Struggle and survival in colonial America - Sweet, David G.; Nash, Gary B. (University of California Press, 1981)
The stories of 23 little-known but remarkable inhabitants of the Spanish, English and Portuguese colonies of the New World. These include women and men of all the races and classes of colonial society.